Penawaran Sayuran Hidroponik Selama Pandemi Covid-19 di Kota Palembang: Faktor-Faktor yang Mempengaruhi dan Elastisitasnya - Adinda Priscilla Salsyah Purba; Desi Aryani; Henny Malini (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Purba, A.P.S., Aryani, D., Malini, H. 2021. Hydroponic vegetables supply during Covid-19 Pandemic in Palembang City: affecting factors and the elasticity. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 465-475. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pakcoy is one of vegetables that are widely cultivated hydroponically which does not require a large area and can be done in the yard of the house. Pakcoy has many benefits so that it can increase the body's immunity, especially during the Covid-19 pandemic that is happening in the world today. The high demand for hydroponic pakcoy during the Covid-19 pandemic is an opportunity for producers or business actors to increase the supply of this vegetable. The purpose of this study was to calculate the income level of hydroponic pakcoy farmers, to analyze the factors that influence supply and knowing the elasticity of hydroponic pakcoy to price and income in Palembang City during the Covid-19 pandemic. The data collection method used an online questionnaire. The data tabulation method used multiple linear regression. The results showed that the average income of hydroponic pakcoy farmers is. 841.862,43 IDR /month which was relatively low. Income and land area partially affected the supply of hydroponic pakcoy positively, while price partially had no effect on the supply. The elasticity of supply to price is Perfectly In-Elastic and the elasticity of supply to income is In-Elastic. The supply of hydroponic pakcoy vegetables from business actors in the city of Palembang is sufficient to keep up with the high demand.